Principal Role In Improve Outcomes for School Values AT-Taqwa SDI Kramat Jegu - Siti Muaisah (Proceedings of The ICECRS, 2017)
This study aims to determine the roleprincipals toimproveschool grades resultsin SDI AT-Taqwa Park.Technique of collecting data is done by interview, observation, and documentation.The data analysis is done with four stages of data collection, data reduction, data presentation, and conclusion.Results from this study is the role of kepala schools in improvingschoolthrough the implementation ofthe results of thereal dutiesof the principal aseducator, manager, administrator, supervisor, leader,innovator, motivator (EMASLIM).Principal as an individual who is responsible in the school is obliged to try to make all the potential that exist in the institution can be utilized as well as possible in order to reach the expected goal.Asdenganimprove teacher qualityofsupervisingthe preparation prior to teaching,learning processes,toassess learning outcomes,and provide specialized training to develop skills inerampilan teachers,to build cooperation conducive to the guardiansof the vision and mission of the school, building facilities and infrastructure to support effective learning.Runningrules and regulations on the SOP to discipline all the activities that have been planned.